The Hard to Catch Mercy : A Novel - Baldwin, William P. (Book collections on Project MUSE., 2015)
From Lowcountry writer William Baldwin comes a new edition of his 1993 Lillian Smith Award--winning novel, The Hard to Catch Mercy. Including a new introduction by the author, this Southern Revivals edition makes available once more a story that touches on the issues of religion, race, and coming-of-age in the post--Civil War South, when the lines between these issues were not always clear. Set in fictional Cedar Point, a small Southern community in the early 1900s, The Hard to Catch Mercy is told through the eyes of a young boy, Willie T., who is forced to confront the changing world around him. Including a cast of incredibly outlandish characters, Baldwin's novel is a wild, darkly comic tale rich with trick mules, Christian voodoo, fire, brimstone, first love, death and the end of the world as Willie T. knows it.